Multicenter analysis of immunosuppressive medications on the risk of malignancy following adult solid organ transplantation - Shaw, Reid; Haque, Ali R.; Luu, Tyler; O’Connor, Timothy E.; Hamidi, Adam; Fitzsimons, Jack; Varda, Bianca; Kwon, Danny; Whitcomb, Cody; Gregorowicz, Alex; Roloff, Gregory W.; Bemiss, Bradford C.; et al. (Frontiers in Oncology, 2023)
Objective: This study aimed to assess the risk of maintenance immunosuppression on the post-transplant risk of malignancy across all solid organ transplant types. Methods: This is a retrospective cohort study from a multicenter hospital system in the United States. The electronic health record was queried from 2000 to 2021 for cases of solid organ transplant, immunosuppressive medications, and post-transplant malignancy. Results: A total of 5,591 patients, 6,142 transplanted organs, and 517 post-transplant malignancies were identified. Skin cancer was the most common type of malignancy at 52.8%, whereas liver cancer was the first malignancy to present at a median time of 351 days post-transplant. Heart and lung transplant recipients had the highest rate of malignancy, but this finding was not significant upon adjusting for immunosuppressive medications (heart HR 0.96, 95% CI 0.72 – 1.3, p = 0.88; lung HR 1.01, 95% CI 0.77 – 1.33, p = 0.94). Random forest variable importance calculations and time-dependent multivariate cox proportional hazard analysis identified an increased risk of cancer in patients receiving immunosuppressive therapy with sirolimus (HR 1.41, 95% CI 1.05 – 1.9, p = 0.04), azathioprine (HR 2.1, 95% CI 1.58 – 2.79, p < 0.001), and cyclosporine (HR 1.59, 95% CI 1.17 – 2.17, p = 0.007), while tacrolimus (HR 0.59, 95% CI 0.44 – 0.81, p < 0.001) was associated with low rates of post-transplant neoplasia. Conclusion: Our results show varying risks of immunosuppressive medications associated with the development of post-transplant malignancy, demonstrating the importance of cancer detection and surveillance strategies in solid organ transplant recipients.